Comprensión estratégica en la organización del discurso. Alusión al congreso del Partido Popular en el discurso de Esperanza Aguirre en el foro de Abc en 2008 - Duque, Eladio (Círculo de Lingüística Aplicada a la Comunicación, 2013)
The article offers an approach to the analysis of relations between strategic comprehension, addressee’s expectations, and the arrangement and function of text parts. The speaker predicts the interpretation of his text; the present analysis, therefore, proceeds from the effort of the one producing discourse, taking into account the way discourse construction is affected by the calculation of addressee’s expectations. The analysis is applied to the reference to the Popular Party Congress made in a speech by Esperanza Aguirre in the newspaper Abc speakers’ forum in 2008.
Keywords: rhetorical structure; discourse organization; expectations; strategic comprehension